PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SUB SEKTOR PROPERTI DAN REAL ESTATE YANG TERDAFTAR BURSA EFEK INDONESIA - Bintari, Wisang Candra; Julyanthry; Wati, Yenny; Debi Eka Putri; Beatrice Chrisna Romaito Sirait (JURNAL EKONOMI PERJUANGAN, 2024)
ABSTRACT. This study aims to describe and analyze the profitability and firm value of companies in the Sub Sector of Property and Real Estate listed on the Indonesia Stock Exchange. Another objective is to understand the impact of profitability on firm value in this industry context. The research utilizes a literature study method with quantitative secondary data. Data is collected through documentation and analyzed using various techniques such as classic assumption tests, simple linear regression, and hypothesis testing. The results indicate that profitability, measured by Return on Assets, fluctuates and tends to decrease. The firm value, measured by Price to Book Value, also fluctuates but tends to increase. Regression analysis shows that profitability negatively impacts firm value. Hypothesis testing results also confirm a low relationship between profitability and firm value